Traditional and complementary medicine practice in Malaysia: A comprehensive review of scientific evidences - Nor Dalila Marican, Nik Alif Amri Nik Hashim, Mohd Hafzal Abdul Halim, Ahmad Fahme Mohd Ali, Naziatul Aziah Mohd Radzi (Journal of Applied Pharmaceutical Science, 2021)
Background: In the Malaysian healthcare system, the juxtaposition of mainstream medicine, which is traditional and complementary medicine (TCM), has now become an essential component. Despite the highly prevalent practice of TCM among Malaysians, the limited evidence of TCM modalities for explicit health conditions has given rise to doubt and controversy within the medical line. This study intends to gather extant scientific evidence of TCM practice in Malaysia which would eventually benefit the complementary and conventional medical profession.Methods: In the pursuit for literature pertaining to the scientific research of TCM in Malaysia, databases that include Science Direct, PubMed, Cumulative Index of Nursing and Allied Health Literature (CINAHL), and Elton B. Stephens Company (EBSCO) host were used to gather the relevant articles comprising all forms of nonexperimental, experimental, and case report data that are limited to the Malaysian population setting.Results: Eight full-text research articles have achieved the inclusion criteria that comprise the trials involving five types of modalities which are medical herbalism, chiropractic, acupressure, aromatherapy, and acupuncture. The most unexplored aspects of designing intervention studies of TCM are the thoughtful and systematic development of treatment protocols. These results point to some potentials for TCM in Malaysian healthcare management in which there is an urgent need for more rigorous research into the value of such treatments.Conclusion: The popularity of TCM has created a need for empirical studies to evaluate the scientific evidence of practice as a method of treatment regime. This study gives a broader summary of the existing literature on the efficiency of TCM for various health conditions which may have an implication for patient care.
Keywords: Traditional medicine, Malaysia, healthcare, effectiveness, efficacy.